Precompetitive assessment of heart rate variability in elite female athletes during play offs. (1st October 2013) - D'Ascenzi, Flavio; Alvino, Federico; Natali, Benedetta M.; Cameli, Matteo; Palmitesta, Paola; Boschetti, Giampaolo; Bonifazi, Marco; Mondillo, Sergio
Summary Background Heart rate variability (HRV) has been rarely applied in elite athletes prior to competition. The aim of this study was to examine the changes in HRV in elite female volleyball players before a stressful match during play offs and to evaluate the impact on sport‐specific performance. Methods A short‐term resting HRV analysis was applied right after the night sleep in ten female athletes 1 and 2 days prior to the match and the day of the competition. Results Approaching the decisive match, RR interval, resting heart rate (HR), pNN50, rMSDD and SD1 did not significantly vary. SD2 significantly increased in comparison with first‐day measurement (P<0·05). HF% levels significantly decreased the prematch day and the match day (P<0·05); however, no significant changes in LF/HF% ratio were observed. A gradual increase in VLF% and in LnVLF was observed, with a significant difference between first‐day and match‐day measurements (P<0·01 and P<0·05, respectively). The number of positive receptions was inversely correlated with LF/HFms2 ratio, with LF/HF% ratio (R = −0·98, P<0·05 for both) and with resting HR (R = −0·92, P<0·05). Conclusions Elite female athletes practising team sports exhibit a slight change in HRV prior to a decisive competition, without a pronounced variation of the autonomic nervous system activity. A day‐to‐day HRV measurement could be a useful tool to evaluate the impact of a competition on the autonomic nervous system in athletes, also considering the relationship between sympathetic activity and athletic performance.